Trends in the Antiviral Chemical Activity of Material Surfaces Associated With the SARS-CoV-2 Outbreak - Schio, Aline Lucchesi; Michels, Alexandre Fassini; Fongaro, Gislaine; Figueroa, Carlos Alejandro (Frontiers in Chemical Engineering, 2021)
The novel coronavirus designated as SARS-CoV-2 has risen the first pandemic caused by coronavirus and by 26 November 2020 is responsible for more than 1,410 million deaths. This scenario evidences that despite previous pandemics and epidemics in the world’s history, the current worldwide measures to contain and to mitigate viruses’ outbreaks are still disabled and insufficient. Therefore, this perspective reinforces the need for new and practical approaches for antiviral materials developments and presents current technologies and its advances in this field of research focusing especially in surface materials since it is one of the most common interaction pathways. Furthermore, it is presented the roll that nanotechnology have been playing in the combat of viruses as well as the mechanisms that science has been discovering to inactivate these pathogenic microorganisms. Finally, we suggest introducing new legislation and norms rather more specified on virucidal agents (materials and devices) than bactericidal ones in human environments such hospitals, nursing homes, buses, shopping centres, etc. to mitigate the current and future virus-based pandemics and epidemics.